Kinetics of Ultrasonic Drug Delivery from Targeted Micelles - Husseini, Ghaleb (2015)
To minimize the adverse side effects of conventional chemotherapy, a targeted micellar drug carrier was investigated that retains hydrophobic drugs in its core and then releases the drug via ultrasonic activation. This paper compares the percent drug release from folated versus non-folated micelles by insonation at 70 kHz and different acoustic power densities. The encapsulated drug is Doxorubicin (Dox). A physical model of zero-order release with first-order re-encapsulation was used to fit the experimental kinetic data. Additionally, the acoustic activation power density and Gibbs free energy were introduced and calculated for folated and non-targeted micelles. The data suggests an important role of inertial cavitation in drug release and the presence of a power density threshold for inertial cavitation.